Explaining "-splain" in digital discourse - Bridges, Judith (Language Under Discussion, 2021)
Combining digital discourse analysis and Citizen Sociolinguistics, methodological frames that contend with the effects of evolving digital practices, I present an approach to studying sociolinguistic trends by investigating how social media users talk about what language is doing. This approach is applicable to research on a wide range of linguistic and cultural contexts. The particular focus in this paper, however, is on U.S.-based social issues and linguistic features of American English as they appear in pieces of digital discourse from the micro-blogging platforms Twitter and Tumblr. Situated within the highly fractured sociopolitical climate of the pandemic-afflicted United States, the language under discussion provides a glimpse of some historically relevant sociocultural beliefs and attitudes towards the role of gender and racial identity in sociopolitical discourse. Focusing on uses of -splain, a metapragmatic bound morpheme, the paper demonstrates how social media users assemble lexical, discursive, and other semiotic resources as means for negotiating sociopragmatic appropriateness. The analysis shows how the usage of words like mansplain encompass the sociolinguistic process of enregisterment through practices of linguistic reflexivity, creativity, and regimentation – practices that are essential aspects of interaction and participation in social media. Using these enregistered metapragmatic words problematizes imbalances in users’ sociopragmatic ideologies, namely who can or cannot say what, to whom, and in what manner. I show how creative metapragmatic language is deployed to discuss issues of entitlement and epistemic authority in communicative dynamics. I draw on theoretical frames that reveal how the recontextualization and resemiotization of -splain words and other metapragmatic neologisms are performances of identity. I also show how splain-mediated communication facilitates users in achieving their own discursive intentions to point out language in judgmental and/or lighthearted manners. I assert that attention to metapragmatic neologisms in the perspective of Citizen Sociolinguistics enhances the analytical repertoire of digital discourse analysis.